Foreign University Students’ Acculturation in the Philippines: A Phenomenological Study - Ledesma, Grezaida; Ledesma, Joseph; Ytang, Feliciano; Songcayawon, Jesse; Acquioben, Edmund; Ibanez, Jeruel; Agum, Arjem Noryn (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Many foreign students go to the Philippines to study. However, studies on foreign students’ adjustment and acculturation were mostly done in non-faith-based institutions before the pandemic. Therefore, this qualitative study aimed to explore the acculturation of foreign students in a faith-based institution in Cavite, Philippines, during the pandemic. Through purposive and snowball sampling techniques, 12 participants were interviewed using a semi-structured interview guide, and the data were analyzed using Colaizzi's method. The results showed that there were similarities and differences in the food and manner of eating and the various practices in the Philippines and their home countries. During the pandemic, the participants were challenged by the online classes, access to basic necessities, and feelings of isolation. They coped with these acculturation challenges through the University’s spiritual programs, personal devotions and initiatives, personnel’s care for students, and care groups. This study found that awareness of the similarities and differences of practices gave students an idea of where to start off in acculturating. Since personnel’s care for students and care groups helped in foreign students’ successful acculturation during the pandemic, it is recommended that universities include in their plan spiritual and social programs and care groups for foreign students. Keywords : acculturation, home country, pandemic, practices, culture